IDENTITAS NASIONAL SUATU BANGSA DAN NEGARA SERTA PERANAN PENTING KONSTITUSI DALAM KEHIDUPAN BERNEGARA - Banna Nidham Ulhaq Banna; Isa Anshori (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
National identity is a sign or characteristic of a country that can distinguish its characteristics from other countries, because the identity of a country lies in the concept of the country itself. Etymologically, national identity comes from the words "identity" and "national". Identity comes from the word identity which means the existence of a character, trait, or quality related to an individual, group, or something that distinguishes it from others. And National comes from the word nation which means state. And every country is obliged to implement constitutional behavior in the life of the state. Because in general the constitution is the basic principle and law of a nation, state, or community group. Where that determines the power, duties of the government and guarantees certain rights for its citizens.